How Did Emerging Markets Cope in the Crisis?. (Policy Papers; Policy Paper ;, 2010)
The IMF Executive Board has been considering reforms to strengthen the Fund's mandate to better equip the institution to safeguard global stability. Executive Directors have supported a range of reforms to modernize the Fund's surveillance mandate and modalities. This paper focuses on selected aspects of these reforms where further work was called for, including on a possible multilateral surveillance decision and proposals to enhance the traction and flexibility of bilateral surveillance.